The influence of fingers’ contracture degree on surgical treatment of Dupuytren’s disease - Stepic, Nenad; Koncar, Jovana D; Rajovic, Milica (Vojnosanitetski pregled, 2017)
Introduction: Dupuytren’s disease is a progressive disease of the palmar and digital fascial structures, with functional limitations. There are no clear statements about the exact time of surgical repair, when hand impairment is concerned. Aim of our study was to investigate the relation between finger’s contracture degree and success of surgical treatment of the Dupuytren's disease . Materials and methods: Prospective analysis of 60 patients operated due to Dupuytren’s contracture. According to preoperative contracture degree of proximal interphalangeal (PIP) and metacarpophalangeal (MCP), patients were divided. Group I: 30°. Postoperative improvement was expressed with contracture reduction INDEX.Results: There were 60 patients with 85 fingers affected. Group I, II and III had 22 (37 %), 37 (62 %) and 26 (43 %) fingers with MCP contracture and 32 (37.4%), 24 (28.2%) and 29 (34.1%) fingers with PIP contracture, respectively. Postoperatively contractures of MCP joint in these groups were 0, 0.135° and 5 °, and 0, 2.08 ° and 16.89°, on PIP, respectively. After six months all MCP contractures resolved, while PIP joint contracture in the group III, was still 13.62°. The reduction INDEX was 98.85%, 97.62% and 75.52% in Group I, II and III, respectively. There was statistical significant difference in the INDEX value between the groups. (p=0.0001).Conclusion: Surgical treatment of PIP joint contractures in Dupuytren’s disease, from 15-30° gives significantly better results than surgical treatment of contractures of greater degree, therefore it might be considered as one of the indications for surgery.Key words: Dupuytren’s disease; contracture degree; fasciectomy